Agenda-Manipulation in Ranking - Curello, Gregorio; Sinander, Ludvig (Review of Economic Studies, 2023)
Abstract We study the susceptibility of committee governance (e.g. by boards of directors), modelled as the collective determination of a ranking of a set of alternatives, to manipulation of the order in which pairs of alternatives are voted on—agenda-manipulation. We exhibit an agenda strategy called insertion sort that allows a self-interested committee chair with no knowledge of how votes will be cast to do as well as if she had complete knowledge. Strategies with this “regret-freeness” property are characterized by their efficiency, and by their avoidance of two intuitive errors. What distinguishes regret-free strategies from each other is how they prioritize among alternatives; insertion sort prioritizes lexicographically.